Pandangan Filosofi Peserta Didik sebagai Insan Kamil (Manusia Utuh) - Maryamah; Prasetya, Akhmad Fajar (CV. SINAR HOWUHOWU, 2025)
Students, from the perspective of the philosophy of guidance and counseling, are viewed as holistic human beings who possess multidimensional potential, encompassing intellectual, emotional, social, moral, and spiritual aspects. This article aims to examine the philosophical view of students as insan kamil (the complete human being) and its relevance to the field of guidance and counseling. The study employs a qualitative approach using a literature review method, drawing on sources from educational philosophy, Islamic philosophy, and guidance and counseling studies. The findings indicate that the concept of insan kamil provides a philosophical foundation for guidance and counseling services oriented toward the holistic development of students’ personalities. Guidance and counseling not only function to assist in problem-solving but also play a role in guiding students toward self-maturity, noble character, and spiritual balance.